Non-equilibrium influence on G/P partitioning of PAHs: Evidence from the diurnal and nocturnal variation. (May 2022) - Zhu, Fu-Jie; Arina, Sun-Zu-Li; Zhang, Zi-Feng; Liu, Li-Yan; Song, Wei-Wei; Cheng, Yuan; Liu, Jiu-Meng; Ma, Wan-Li
Abstract: Gas/particle (G/P) partitioning is an important behavior for the atmospheric transport of polycyclic aromatic hydrocarbons (PAHs). In this study, paired daytime and nighttime air samples were collected for one year in order to study the diurnal and nocturnal variations of concentration and G/P partitioning of PAHs. Higher PAHs concentrations in total phase were observed in nighttime. The geomean (GM) concentrations of Σ15 PAHs in total phase were 69.6 and 52.8 ng/m 3 in nighttime and daytime, respectively. More obviously diurnal and nocturnal variations were observed in non-heating season, with the GM ratios of Σ15 PAHs in nighttime to daytime of 1.65 and 1.06 in non-heating season and heating season, respectively. The results could be attributed to emission sources and meteorological conditions. The values of particulate phase fraction ( ϕ P ) and G/P partitioning quotient (log K P ) were used to quantify the phase distribution of PAHs. For most high molecular weight PAHs, the values of ϕ P and log K P in nighttime were higher than those in daytime, which could be mainly attributed to the lower temperature in nighttime. However, for the three light molecular weight PAHs (Acy, Ace and Flu), higher values of ϕ P and log K P were observed in daytime. The regression of log K P against log K OA for the three PAHs in daytime differed from those in nighttime. The chemical losses of PAHs in different phases might be responsible for the result. These findings suggested that the chemical loss of PAHs in gas phase should be considered for the G/P partitioning process. Graphical abstract: Image 1 Highlights: Higher PAHs concentrations were found in nighttime than daytime in non-heating season. More obvious diurnal variation of PAHs concentration was observed in non-heating season. Higher values of ϕ P and K P for high molecular weight PAHs were found in nighttime. G/P partitioning of light molecular weight PAHs might be affected by chemical loss in gas phase.